Subjective implications of experiencing pregnancy and the diagnosis of cardiopathy of a son: psychoanalytic contributions to women’s health - Cavalcante Teixeira, Leônia; Mualem Sousa de Moraes, Wecia (O Mundo da Saúde, 2008)
Fertilization, gestation and the birth of a son are processes marked by intense experiences in the subjective domain. When a congenital damage is diagnosed in the son, be it in uterus or after birth, complex mourning processes are mobilized before the loss of the idealized son, making it difficult for mothers to invest i the gestation and in the experience with their baby. The discovery of a cardiopathy in the son creates in mothers a narcissist injury, and puts her, together with the baby, in a condition of organic and psychological risk. Mother-child health constitutes a focus in care and management policies of the Ministry of Health, and are implemented by Programs such Integral Assistance to Women’s Health and Broadened Clinic. The general aim of this inquiry was to analyze subjective repercussions a son with congenital cardiopathy cause in mothers, and was carried out in the Instituto do Coração da Criança e do Adolescente (Institute of Heart of the Child and the Adolescent) in Fortaleza - CE. Theoretical based on an interface of knowledge and practices of biomedicine and psychoanalysis. The reports were interpreted considering the subjective implications of the experience of pregnancy and the diagnosis of cardiopathy of a son. We conclude that the diagnosis of a congenital damage in a son implies processes of acceptance of loss of the ideal and of subjective investment in the son who demands cares and support. We emphasize research and interdisciplinary interventions in the consolidation of policies that consider the subjective aspects of reproductive health and its ups and downs in the contexts of health teams and the family, emphasizing the importance of sociability networks in social policies.